Gastrointestinal parasite infections in fighting bulls in South Thailand - Kaewnoi, Domechai (Vet World, 2020)
BACKGROUND AND AIM: Bullfighting is booming in South Thailand, attracting tourists, and stimulating local economies. The bulls are well raised and practiced, but in many cases, the owners lack knowledge and understanding of the prevention of animal diseases, including parasitic infections. This study aimed to determine the occurrence of gastrointestinal (GI) parasite infection in fighting bulls. MATERIALS AND METHODS: A total of 1501 fecal samples were collected from bulls aged 2-5 years visiting the animal hospital of Prince of Songkla University during 2016-2019. The formalin ethylether concentration method was used to detect GI parasites in feces. RESULTS: The overall rate of GI parasite infection was 94.27%. Rumen fluke eggs were detected in 97.17% of all infected animals, followed in prevalence by strongyles (26.29%), Eurytrema spp. (2.83%), Fasciola spp. (2.47%), Trichuris spp. (0.35%), and Moniezia spp. (0.14%). Two protozoan genera were identified, Balantidium coli (6.64%) and Eimeria spp. (3.53%). Coinfection was observed in 33.99%. The five most common coinfections were rumen fluke with strongyles (20.85%), B. coli (4.66%), Eimeria spp. (1.55%), Eurytrema spp. (1.34%), and Fasciola spp. (1.06%). CONCLUSION: In addition to high GI parasite infection rates, zoonotic parasites were observed. Therefore, it is recommended that farmers should follow good sanitation and prevention practices to control parasitic infections in bulls, and proper hygienic precautions should be taken by the owners. Implementation of deworming programs using appropriateanthelmintic drugs as well as rotation of anthelmintic drug that have different chemical agent to prevent further drug resistance should be considered. The promotion of bull health management is highly recommended to protect humans from zoonotic diseases.